FIGURE 7 in Bivalves from the latest Jurassic-earliest Cretaceous hydrocarbon seep carbonates from central Spitsbergen, Svalbard - Hryniewicz, Krzysztof; Little, Crispin T.S.; Nakrem, Hans Arne (Zenodo, 2014)
FIGURE 7. (A–F) Mesosaccella rogovi sp. nov. (A–B) Lateral view of a internal mould showing pallial line. Fragment of the shell shows concentric growth lines. (C) Dorsal view of specimen with partially preserved shell showing weak carina, escutcheon, unidentified muscle scars and ridges formed by growth line deflections. (D–E) Lateral view of right valve internal mould showing weak posterior adductor muscle scar and weak pallial line with very shallow pallial sinus. (F) Internal view of the right valve showing anterior and posterior dental rows and cardinal dentition. (G–P) Mesosaccella toddi sp. nov. (G–K) Left valve lateral views of articulated specimens. (J) Details of external ornament showing characteristic commarginal ridges and rosette-shaped ornament in interridge spaces (arrowed). (K) Holotype showing strong posterior carinae. (L–M) Anterior and posterior views of holotype. Note three carinae and escutcheon visible in the posterior view. (N) Dorsal view of holotype showing three carinae and their relation to wide and shallow escutcheon. (O) Internal view of the dorsal margin of articulated specimen showing cardinal-most teeth and unidentified muscle scars. (P) Lateral view of right valve internal mould showing relatively strong, circular anterior adductor muscle scar and elongated posterior adductor muscle scar, as well as strong pallial line with shallow pallial sinus. (A–E) PMO 217.371, (F) PMO 217.539, (G) PMO 217.609, (H) PMO 217.610, (I–J) PMO 217.616, (K–N) PMO 224.861, (O) PMO 225.031, (P) PMO 224.862. Scale bars 5 mm (A–F, K–P), 2 mm (G–I). : Published as part of Hryniewicz, Krzysztof, Little, Crispin T.S. & Nakrem, Hans Arne, 2014, Bivalves from the latest Jurassic-earliest Cretaceous hydrocarbon seep carbonates from central Spitsbergen, Svalbard, pp. 1-66 in Zootaxa 3859 (1) on page 19, DOI: 10.11646/zootaxa.3859.1.1, http://zenodo.org/record/4930112